Improving Student Reading Literacy Through the Thematic Reading Corner Assistance Program at SDN 42 Ternate City - Rohana Sufia; Hernita Pasongli; Iksan Iksan; Joko M. Jen (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
The results of the situation analysis revealed that the condition of the library at SDN 42 Kota Ternate was not optimal, and students' interest in reading was still low. In facing this challenge, the PkM program created a solution by creating a thematic reading corner that aims to stimulate students' interest in reading and increase their literacy. The method used is action research which emphasizes the active participation of all parties involved, including students and teachers. In the process, servants along with teachers and students are actively involved in the development, implementation, and evaluation of this program. Various activities have been carried out, such as outreach, setting up reading corners, and training to increase reading interest. The results show an increase in students' interest in reading, as well as a positive response to the existence of a reading corner. With these results, the PkM program objectives have been achieved. Overall, this PkM program provides an overview of initiatives that focus on increasing students' literacy and in reading interest can have a positive impact. Through collaboration between servants, teachers, students, and school partners, this program has succeeded in creating solutions that are relevant to school and community conditions at SDN 42 Ternate City.